2014
DOI: 10.4321/s0213-61632014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Suicide, unemployment and other socioeconomic factors: evidence from the economic crisis in Greece

Abstract: GREECEABSTRACT -Background and Objectives: Economic adverse conditions are acknowledged as having a major impact on the exacerbation of mental disorders and suicides. The severity of current European crisis and the local unrelenting spending is affecting largely the economy of Greece.Methods: The aim of this study was to explore changes in suicides and their possible association with macroeconomic and behavioural factors. Data for the period 1990-2011 were drawn mainly from the Hellenic Statistical Authority a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 41 publications
1
50
0
8
Order By: Relevance
“…16 Studies in Greece showed an increase in the total number of suicides in the early years of the economic crisis between 2008 and 2011, 17,18 and a significant increase in prevalence in reported suicide attempts and suicidal ideation during the same period. 10,19,20 More specifically, in Greece the number of suicide deaths increased by 55.8% in 2007-2011, although the total mortality rate increased by only 1.1% 21 in the same period. Concerning the impact of financial conditions on suicide, correlations of changes in suicide rate with the unemployment rate and the amount of the public debt were found 21 during the same period.…”
Section: The Impact Of Unemployment On Mental Health Examined In a Comentioning
confidence: 99%
See 1 more Smart Citation
“…16 Studies in Greece showed an increase in the total number of suicides in the early years of the economic crisis between 2008 and 2011, 17,18 and a significant increase in prevalence in reported suicide attempts and suicidal ideation during the same period. 10,19,20 More specifically, in Greece the number of suicide deaths increased by 55.8% in 2007-2011, although the total mortality rate increased by only 1.1% 21 in the same period. Concerning the impact of financial conditions on suicide, correlations of changes in suicide rate with the unemployment rate and the amount of the public debt were found 21 during the same period.…”
Section: The Impact Of Unemployment On Mental Health Examined In a Comentioning
confidence: 99%
“…10,19,20 More specifically, in Greece the number of suicide deaths increased by 55.8% in 2007-2011, although the total mortality rate increased by only 1.1% 21 in the same period. Concerning the impact of financial conditions on suicide, correlations of changes in suicide rate with the unemployment rate and the amount of the public debt were found 21 during the same period. A significant impact of unemployment, economic distress and low educational level on suicidal ideation and suicide attempts was also detected by a country-wide epidemiological study in 2013.…”
Section: The Impact Of Unemployment On Mental Health Examined In a Comentioning
confidence: 99%
“…Most of those reports are based on scientific research findings. From the very early and sometimes poorly justified papers Madianos et al 2011;Chang et al 2013) to the more recent works (Rachiotis et al 2015;Branas et al 2015;Antonakakis and Collins 2014;Madianos et al 2014;Gatopoulos 2013), suicides -in absolute numbers as well as in rates -have skyrocketed in response to increasing joblessness, serious income setbacks, health deterioration and depression. Yet this relationship is rather speculative, since neither the nature of the data nor the methods applied allow for establishing causality.…”
Section: Introductionmentioning
confidence: 99%
“…Madianos et al12 reported that suicide mortality rates were increased by 55.8% between 2007 and 2011, when the austerity measures were implemented, while the total mortality was increased by only 1.1%. Similar results were reported by Rachiotis et al13 who found that the suicide rates overall increased by 35% between 2010 and 2012.…”
Section: Discussionmentioning
confidence: 99%